PENGARUH PEMBERIAN RELAKSASI PROGRESIF TERHADAP INTENSITAS NYERI PADA PASIEN KANKER PAYUDARA POST PEMBEDAHANMASTEKTOMI DI RSUD PROF. Dr. MARGONO SOEKARJO PURWOKERTO - Maria Yuga Puspitasari; Atun Raudotul Ma’rifah; Maria Paulina I.S (Viva Medika, 2015)
Background: Breast cáncer is a scary disease for women since the overgrowing of breast cell willcréate the bump in the breast. Breast cáncer patiens can not recover 100% eventhough they havedone the surgery. The frequency complaint which appears on breast cáncer patients after doingsurgery is the pain. Thus,special treatment is needed this problema. The relaxation programfocused in the mind makes the respondents feel calm and the pain is also reduced. Objective: The aim of the research was know the effect of giving progressive to pain intensity onbreast cáncer patients post mastectomy surgery in RSUD Prof. Dr. Margono Soekarjo Purwokerto.Method: Theresearch used quasi experimental design with pretest-posttest draft in two groups. Thesample were taken using accidental sampling technique with 38 respondent who are divided intotwo groups, action group 19 respondents and control group 19 respondents. The instrument of thisresearch was Numerical Rating Scale (NRS). Result: Based on the result of the research using Wilcoxon Signed Rank Test, it can be obtained thevalue of p 0,000 (p<0,05), Z arithmetic = -3,938 > Z table = -1,96. Statistic test Man Withney Uvalue p 0,000 (p<0,05), Z arithmetic = -5,218 > Z table = -1,96.Conclusion: Therefore progressive relaxation can be applied in nursing intervention to overcomethe paintl. Keywords: progressive relaxation, paintful intensity, post mastectomy surgery.